Coronary artery anomalies in North Indian population : a conventional coronary angiographic study - Yogesh Diwan; Deepa Diwan; Randhir S Chauhan; Prakash C Negi (Wolters Kluwer Medknow Publications, 2017)
Background: Anomalies of origin and course of one or both coronary arteries, with or without symptoms, are of special interest for anatomists, interventional cardiologists, and cardiac surgeons. Aims: To estimate the prevalence of coronary anomalies and their clinical aspects in North Indian population. Material and Methods: Study was done on patients undergoing coronary angiography for suspected coronary artery disease or for coronary intervention at a tertiary care centre in North India. Results: A total of 1130 patients [803 males, 327 females and mean age 57.37±10.60 years] were reviewed for coronary artery anomalies. Overall incidence of Coronary artery anomalies was 13 [1.15%] and was 1 % in men and 1.53% in women. 38.46% of these patients were found to have ectopic origin of left circumflex [LCx] and in 23.08% of cases, ectopic origin of right coronary artery [RCA] was noted. Separate orifice for left anterior descending [LAD] and LCx in left coronary sinus [LCS] was observed in 0.27% cases, coronary artery fistula [CAF] in 0.09% cases and single coronary artery from LCS was found in 0.09% cases. Conclusions: The most common coronary anomalies were origin of LCx from RCA and presence of separate orifice for LAD and LCx in LCS. Dominance, gender and coronary artery disease [CAD] have no association with coronary anomalies.